IMPLEMENTASI KEBIJAKAN PROGRAM PELATIHAN KERJA DINAS KETENAGAKERJAAN DAN TRANSMIGRASI KOTA SUKABUMI - Sidik, Ardi Muhammad (Administratio, 2019)
ABSTRACT The title of this research is "Implementation of the Job Training Program Policies of the Manpower and Transmigration Office of Sukabumi City". The implementation of the job training program is based on regulation of mayor no. 71 of 2016 on the Technical Implementation Unit of the Training Center at the Department of Manpower. The implementation of the job training program encountered several problems, namely the lack of staffing staff and the lack of adequate facilities and infrastructure. This research uses the theory of public policy implementation according to Edward III. The purpose of this study is to know the implementation of the policy and the factors that hinder and support its implementation, with informants amounted to 6 people. This research uses descriptive qualitative research method. Data obtained through observation, interview, documentation, and triangulation. The data validity testing procedure is done by triangulation of source data analysis process using model proposed by Miles and Huberman. The results revealed that the implementation of training program policies have not run optimally due to lack of instructors training and infrastructure facilities are inadequate. Suggestions that researchers provide to optimize the policy that is necessary to add equipment that can be pursued by requesting the submission of additional to the government. The need for additional instructors with the request of instructors to the central government. It also can temporarily receive the honorary instructor according to the qualification of the instructor. Keywords: Implementation, Job Training Program